Full-mouth aesthetic rehabilitation: A perio-prostho interdisciplinary approach - Arnav Mukherji; Saroj Kumar Rath (Wolters Kluwer Medknow Publications, 2015)
Crown lengthening is a surgical procedure aimed at the removal of periodontal tissue to increase the clinical crown height. The clinician needs to have an understanding of the biological width, indications, technique as well as limitations regarding crown lengthening. Taking into account the biological factors, crown lengthening can be carried out in a controlled and predictable manner as part of an overall treatment plan. Today's dentist has to face an increase in the number of patients who exhibit wearing of teeth that might result in shortened teeth, which makes the creation of crowns for these teeth problematic. In addition, it is evident that patients are becoming more aware of the importance of a pleasing smile. This case report discusses surgical crown lengthening of attrited teeth for adequate prosthetic restoration.